Caracterización fisiológica y física del recubrimiento órgano-mineral de la semilla de chocho (lupinus mutabilis sweet) utilizando tres tipos de polímeros. - Quishpe Quishpe, Sonia Marisol (2020)
The research was carried out in the laboratory of Agricultural Engineering at the Technical University of Cotopaxi, at an altitude of 2725 m.a.s.l. and coordinates 00°59'57'' south latitude and 78°37'14'' west longitude, with the objective of characterized and physically the organomineral coating of the chocho seed (Lupinus mutabilis sweet). It was applied an experimental design with a 3*2 +1 factorial arrangement, giving a total of 7 treatments and 21 experimental units. Three organic polymers were used: Chitosan (Qt), Sodium Alginate (Alg), and Potato Starch (Alp), as part of the organo-mineral coating: Cow manure (Esv) + Zeolite (Ze), Humus (Hm) + Phosphate rock (Rf). The T6 Treatment (Alp + Hm +Rf) registers better results in relation to physiological processes. In the case of germination percentage (PG) 83.33%, emergency speed index (IVE) 82.3%, radicle length (LR) 11.48 cm, plumule length (LP) 12.48 cm and physically with a hardness 84 kg/cm2 excellent range of hardness, buoyancy 0.22 m / water absorption capacity of 19ml, capacity of inert materials 42.89 ml. It is concluded that better results in the physiological processes and physical characteristics of the coating are obtained with the T6 (Alp+ Hm + Rf) treatment parameters based on our decision table recorded in the document.